Poisoning suicide with ingestion of the pyrethroids alpha-cypermethrin and deltamethrin and the antidepressant mirtazapine: A case report. (May 2017) - Boumba, Vassiliki A.; Rallis, Georgios N.; Vougiouklakis, Theodore
Abstract: This case report describes a death attributed to the intake of the pyrethroid insecticides, alpha-cypermethrin and deltamethrin, and the antidepressant mirtazapine. The autopsy findings showed absence of external traumatic injuries and internal generalized visceral congestion, edema and cyanosis. The toxicological results revealed the presence of a toxic concentration of mirtazapine (12.5 mg/L and 10.7 mg/L in blood and urine, respectively) and high concentrations of pyrethroids (2.46 mg/L alpha-cypermethrin and 2.40 mg/L deltamethrin in blood, and 0.41 mg/L alpha-cypermethrin and 0.46 mg/L deltamethrin in urine, respectively). Blood ethanol concentration was 0.75 g/L. All the evidence – from autopsy, police investigation and toxicology – was consistent with the intentional self-harm of the deceased. The current case was determined and recorded as a poisoning suicide. Cause of death of the deceased was reported as the synergistic toxicity of the ingested pyrethroids and mirtazapine. The presence of a significant blood ethanol concentration was considered a secondary contributory factor to the fatal outcome. The case presented herein is the first death attributed to poisoning from ingestion of pyrethroids in combination with mirtazapine, with the intention of the victim to cause self-harm, with corresponding toxicology results.